Positive impact of the Therasuit method on gross motor function of children with autism spectrum disorder: Case series - Baptista, Pedro Porto Alegre; Furtado, Ana Carolina Azevedo; Fernandes, Tiótrefis Gomes; Freire Júnior, Renato Campos; Lima, Cristiana Freitas Miranda; Mendonça, Ayrles Silva Gonçalves Barbosa (Frontiers in Neurology, 2023)
The Therasuit method is a valuable physiotherapeutic method to improve the gross motor function of children with neuromotor disorders. This series of case studies investigates the effect of the Therasuit method on the gross motor function of children with autism spectrum disorder (ASD). Therasuit method is a therapeutic intervention that involves the use of a therapeutic suit attached to a cage to stimulate gross motor skills, muscle strengthening, stretching, task training, and balance, which is a positive intervention for other neurodevelopmental disorders. The study was conducted with nine male children (42.1 + 4.1 months old) with ASD who received the Therasuit protocol for 4 weeks (20 sessions). The Gross Motor Function Measure (GMFM-88) was used to assess the children’s gross motor function before and after the Therasuit method intervention. In dimension B, several skills showed improvement, including transfer to sitting, lean forward and return, trunk rotation without support, and transfer from sitting to all four stances. In dimension C, an increase was observed in skills such as being prone to all four stance transfers and reaching above the shoulders. In dimension D, maximum scores were achieved in skills such as pulling to stand on a large bench without assistance. The dimensions with the greatest impairment were D and E, corresponding to gross motor skills in orthostasis and dynamic skills in orthostasis, respectively. The findings suggest that the Therasuit method is a promising resource for treating motor impairments in children with ASD. However, further studies with a larger sample size, an adequate control condition, and random assignment of participants would be needed to provide stronger evidence of the method’s effectiveness in this population.